Crossroads of aspiration: unveiling the migration intentions among university students in North Macedonia - Katerina Shapkova Kocevska; Biljana Tashevska; Marija Trpkova - Nestorovska; Suzana Makreshanska Mladenovska (Stanovništvo)
In our work, we analysed the migration intentions of university students from North Macedonia. We used data from a survey with 412 students from the Ss. Cyril and Methodius University in Skopje, the country’s largest and oldest university. The results showed that about two-thirds of the respondents (67 per cent) intend to emigrate. To identify the determinants of the migration intentions, we used logistic regression models, where the migration intention was the dependent variable. We used different sets of socio-demographic and educational variables, the economic status of the respondents, and other factors as independent variables. Exploratory factor analysis was used to identify the following factors: Housing, environment, and public services; Social activities and community engagement; Advanced and developed society; Enhanced educational and career opportunities; Public services; Economic and social progress; and Family and social well-being. All of them, except the last one, had a statistically significant impact on the students’ intentions to emigrate. Moreover, the students with more educated parents, students with higher academic performance and the students who worked had higher odds of emigrating than the students with parents with lower educational levels, students with lower academic performance and the students who didn’t work while they studied, respectively. The other socio-demographic, educational and economic variables were not statistically significant.